EVALUATION OF CONSUMPTION OF NATURAL PRODUCTS BY USERS OF THE STRATEGIES OF THE COUNTY FAMILY HEALTH RONDONOPOLIS - MT - Lara, Ana Caroline de; Oliveira, Cristiane Melo; Mendes, Vanessa Alves; Stocco, Patricia; Ferro Hein, Milene Moreno; Favero Lisboa, Helen Cristina [UNESP] (Univ Vale Paraiba-univap, 2019)
The use of plants in popular practices has been known since prehistory, and has now been called complementary medicine. In the last decade, there has been an increase in the use of alternative therapeutic practices supported by policies within the scope of the Sistema Unico de Saude (SUS), in particular the use of medicinal plants and herbal medicines. In this sense, the present study aimed to assess the use of medicinal plants and herbal medicines by users registered in the Family Health Strategies in Rondonopolis, MT. This is a quantitative research, in which interviews were conducted by questionnaires. From the 71 people interviewed, 63% do not know the difference between herbal and medicinal plants, plants, 58% know the different ways of using the plants, 45% drink them as tea, and the part of the plant preferred by consumers are the leaves (59%). Approximately 44% had not conducted any type of consultation before consumption and 48 people made concomitant use of synthetic drugs. Considering the results obtained, it is verified that there may be increased risks of intoxication and adverse reactions; therefore, there is the need for correct and accurate guidance regarding the use of natural products.
Keywords: Herbal medicine; phytotherapics; natural products